Industry 4.0 Powered Process Technology Innovation, Firm’s Leanness, and Eco-Environmental Performance During the COVID-19 Phase - Sun, Han; Chu, Xiao (Frontiers in Environmental Science, 2022)
Amid rising market competitiveness, Industry Revolution (IR) 4.0 oriented technological integration considers an imperative driver of sustainable organizational performances and facilitating green supply chain management. Recognize the same; this study explores the role of IR 4.0 powered process technology innovation in enhancing Leanness, Green Supply Chain Management, and Organizational Performance (including operational, economic, and environmental) during COVID-19. For this purpose, a novel conceptual framework was developed, and Partial Least Square-Structural Equation Modelling (PLSM) was employed on primary data of 314 respondents collected from Chinese manufacturing industries. Moreover, Multi-Group Analysis was also implemented to compare firm’s willingness to implement IR 4.0 technologies powered process innovation. The results exhibit that Green IR 4.0 powered process technology innovation improves the firm’s leanness that resultantly stimulates the firm’s environmental, optional, and economic performances. Similar findings are endorsed through the green supply chain management channel. Manifestly, COVID-19 instigated firms to adopt IR 4.0 based technological processes for the efficient supply chain management. Based on these results, organizations are recommended to integrate the IR 4.0 induced technology innovation to spur manufacturing firms' eco-economic and operational performance.